Mengurai Kedalaman Makna Melalui Metafora: Analisis Puitis Pengarang - Sule Rabani; Irena Suleha (Lembaga Pengembangan Kinerja Dosen, 2024)
Poetry is a form of literary work that is full of meaning and beauty, as a result of protective expressions and feelings that are bound by certain elements such as rhythm, meter, rhyme, lyric composition, and stanzas. In this study, we investigate the meaning of metaphors expressed by authors in poetry. Lafamane (2020:1) and Sumardi (in Lafamane:2020) emphasize that poetry is condensed, shortened and given rhythm with imaginative figurative words. Herbert Spencer (in Lafamane: 2020) added emotional dimensions and beauty as important elements in poetry. Thus, the meaning of metaphor in poetry explores the emotional depth and beauty expressed by the author through figurative language that captivates the reader. Through analyzing the meaning of metaphor, we can understand more deeply the essence of poetry and the richness of the author's imagination in conveying messages beautifully and captivatingly.